Clinical thresholds in pain-related facial activity linked to differences in cortical network activation in neonates. Issue 5 (27th May 2023) - Bucsea, Oana; Rupawala, Mohammed; Shiff, Ilana; Wang, Xiaogang; Meek, Judith; Fitzgerald, Maria; Fabrizi, Lorenzo; Pillai Riddell, Rebecca; Jones, Laura
Abstract : Supplemental Digital Content is Available in the Text. Subclinical and clinically significant pain-related facial expressions in neonates are related to distinct patterns of early cortical network activation after a noxious stimulus. Abstract: In neonates, a noxious stimulus elicits pain-related facial expression changes and distinct brain activity as measured by electroencephalography, but past research has revealed an inconsistent relationship between these responses. Facial activity is the most commonly used index of neonatal pain in clinical settings, with clinical thresholds determining if analgesia should be provided; however, we do not know if these thresholds are associated with differences in how the neonatal brain processes a noxious stimulus. The objective of this study was to examine whether subclinical vs clinically significant levels of pain-related facial activity are related to differences in the pattern of nociceptive brain activity in preterm and term neonates. We recorded whole-head electroencephalography and video in 78 neonates (0-14 days postnatal age) after a clinically required heel lance. Using an optimal constellation of Neonatal Facial Coding System actions (brow bulge, eye squeeze, and nasolabial furrow), we compared the serial network engagement (microstates) between neonates with and without clinically significant pain behaviour. Results revealed a sequence of nociceptive cortical network activation that was independent of pain-related behavior; however, a separate but interleaved sequence of early activity was related to the magnitude of the immediate behavioural response. Importantly, the degree of pain-related behavior is related to how the brain processes a stimulus and not simply the degree of cortical activation. This suggests that neonates who exhibit clinically significant pain behaviours process the stimulus differently and that neonatal pain-related behaviours reflect just a portion of the overall cortical pain response.